Anti‑inflammatory effect of red ginseng marc, Artemisia scoparia, Paeonia japonica and Angelica gigas extract mixture in LPS‑stimulated RAW 264.7 cells. Issue 1 (2022) - SHIN, JAE YOUNG; KANG, EUN SEO; PARK, JI HYEON; CHO, BYOUNG OK; JANG, SEON IL
No abstract available